2019
DOI: 10.1021/acs.jpcc.9b00943
|View full text |Cite
|
Sign up to set email alerts
|

Probing Facet-Dependent Surface Defects in MAPbI3 Perovskite Single Crystals

Abstract: Halide perovskites such as methylammonium lead iodide (MAPbI 3 ) currently attract considerable attention because of their excellent optoelectronic properties and performance in solar cell devices. Despite tremendous research efforts to elucidate their fundamental properties, ion migration with the presence of ionic defects is still not fully understood. Here, various types of ionic defects for specific (100) and ( 112) lattice facets in single-crystal MAPbI 3 have been investigated systematically. Our measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 52 publications
3
101
1
Order By: Relevance
“…[ 216 ] Facet‐dependent photoluminescence of MAPbI 3 has been investigated by Kim et al by exciting the (100) and (112) crystal facets of large MAPbI 3 single crystals. [ 182 ] As described in more detail in Section 3.3, the authors observed differences in both the PL intensity and peak position between the different crystal facets. These differences were ascribed to facet‐dependent defect types, which leads to variations in nonradiative recombination and marginal changes in the bandgap.…”
Section: Composition Defects and Microstructure And Their Impact Onmentioning
confidence: 97%
See 1 more Smart Citation
“…[ 216 ] Facet‐dependent photoluminescence of MAPbI 3 has been investigated by Kim et al by exciting the (100) and (112) crystal facets of large MAPbI 3 single crystals. [ 182 ] As described in more detail in Section 3.3, the authors observed differences in both the PL intensity and peak position between the different crystal facets. These differences were ascribed to facet‐dependent defect types, which leads to variations in nonradiative recombination and marginal changes in the bandgap.…”
Section: Composition Defects and Microstructure And Their Impact Onmentioning
confidence: 97%
“…Kim et al measured the facet‐dependent emission (λ exc = 409 nm, one‐photon excitation) on MAPbI 3 crystals grown by the inverse temperature crystallization process, showing a strong anisotropy of properties, which they attributed to native point defects. [ 181,182 ] They found that the emission intensity from the (112) crystallographic facet is reduced and red shifted when compared to the (100) facet; these occur at 784 and 776 nm, respectively. In order to understand how defects play a role in this effect they measured the contact potential difference (CPD) of the two facets by scanning kelvin probe force microscopy.…”
Section: Composition Defects and Microstructure And Their Impact Onmentioning
confidence: 99%
“…We acquired temperature-dependent capacitance versus frequency (C-f) plots to probe trap density and the energy depth of trap states (see supplementary materials). AALs have the potential to suppress trap density directly by filling in A-site vacancies and modifying grains and interfaces; additionally, they have the potential to provide a similar benefit by promoting the (100) orientation of grains in perovskite films 60 , which may have a different susceptibility to surface-defect formation than other random orientations in the pristine perovskite films 61,62 . To further investigate this possibility, we studied the dependence of trap density on the surface crystallographic facets using density functional theory (DFT) calculations based on a cubic FAPbI3 model 63,64 .…”
Section: Mechanisms Underpinning Efficiency Enhancementsmentioning
confidence: 99%
“…This is called the anisotropy phenomenon. It was reported that the (100) and (112) facets of the MAPbI 3 single crystal exhibited different ion migration behaviour and defect status [42]. The I − vacancy dominated (100) facet followed n-type behaviour, while the (112) facet displayed p-type behaviour with MA + and Pb 2+ dominance.…”
Section: Properties Of Single Crystalsmentioning
confidence: 99%